PENGGUNAAN MEDIA FILM ANIMASI UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS V SDN 110 PEKANBARU - Rifka Christy Berutu (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This research is a classroom action research. The purpose of the study was to improve student writing skills of narrative text in elementary school V 110 grade Pekanbaru using animated movies. Data collection techniques are observations and writing tests. Data analysis is quantitative and qualitative. On the initial data the average value is 63.42, where there are no student’s who get grades in the highly skilled category, and 3 students get grades in the skilled category. In cycle I the average value increased to 75.79, where 1 student get grades in the highly skilled category and 27 students get grades in the skilled category and the percentage of research success was 73.68%. In cycle II The average value also increased to 82.23, where 6 students get grades in the highly skilled category and 31 students get grades in the skilled category with a percentage of research success was 97.37%. So it can be concluded that the use of animation movies as media can improve the writing narrative text skill students of grade V SDN 110 Pekanbaru.